Evaluation of the Effectiveness of the Customer Focus Theory Method in Product and Service Development - Fajri, Ratu Chaterine; Agustin, Maulina (Institut Teknolog dan Bisnis Diniyyah Lampung, 2025)
This research originates from the increasing competition in e-commerce, which is becoming more complex as the digital marketplace grows. The main objective of this study is to explore the key elements of a customer-oriented competitive strategy and analyze its impact on marketing performance. Case studies were conducted on two leading platforms, Shopee and TikTok Shop, using the Customer Focus Theory Analysis method. This approach enables an in-depth investigation of consumer preferences, needs, and behaviors, as well as how these factors influence competitive strategies and marketing performance. The research findings are expected to provide a holistic understanding of the application of customer focus concepts in competitive strategies and offer practical guidance for e-commerce practitioners to enhance their competitiveness.